Autonomous Rescue Hexapod Robot with AI Human Detection and Tracking - Chissanupong Saengsint; Kidtipod Juntacheevakul; Kirawut Chalermkitpaisan; Napak Suthapintu; Pavares Tomaneenilrat; Navavee Jungwongsuk; Sarucha Yanyong; Poom Konghuayrob; Supun Dissanyaka (My University, 2023)
The occurrence of catastrophic caused tons of thousands of lives. To enhance the efficacy of search and rescue operations in challenging to access region, we have introduced an autonomous hexapod robot equipped with a partial human detection and tracking system that is capable to identify fragments of the human body. The chosen hexagonal arrangement of six legs enables the robot to navigate through rough terrains. This configuration provides stable mobility, with an average acceleration of 0.8 m/s 2 and a peak acceleration of 3.1 m/s 2 during walking, making the camera of the robot remains steady for human identification. Due to the employed DeeplabV3+ architecture for the training process, partial human bodily structure detection has achieved 94% accuracy. Moreover, the robot can track the detected individual by maintaining 1m distance.
Keywords: Robotic Locomotion and Control; Prosthetics and Rehabilitation Robotics